2022
DOI: 10.1002/app.52298
|View full text |Cite
|
Sign up to set email alerts
|

Effects of composite reinforcing filler, vulcanizing temperature, and pressure on mechanical properties of gasket material for proton exchange membrane fuel cells

Abstract: Gasket is one of the key components in proton exchange membrane fuel cells (PEMFCs), and the performance of the gasket can directly affect the durability and electrochemical performance of the PEMFCs. In this paper, the silicone rubber material, which is being considered as gasket material for PEMFC, was fabricated with different composite reinforcing fillers at different vulcanizing temperatures under different vulcanizing pressures. Effects of the composite reinforcing fillers (i.e., gas-phase SiO 2 and nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In these cases, the number of generated radicals is enough to compensate the temperature effect and overlap it. Hou et al [ 45 ] recently reported the same effect of temperature on the optimum cure time for dicumylperoxide-crosslinked silicone rubber.…”
Section: Resultsmentioning
confidence: 80%
“…In these cases, the number of generated radicals is enough to compensate the temperature effect and overlap it. Hou et al [ 45 ] recently reported the same effect of temperature on the optimum cure time for dicumylperoxide-crosslinked silicone rubber.…”
Section: Resultsmentioning
confidence: 80%
“…Therefore, excellent mechanical stability has to be enrolled as one of the prerequisites. 11,12 The operating temperature of fuel cell stacks ranges from À30 to 95 C, and the sealing material must possess good chemical and mechanical resistance under varied temperatures. 13,14 Tan et al, 15,16 Lin et al, 17,18 and Qiu et al 19 studied the performance and durability of state-of-the-art sealants applied in PEMFC, including silicone rubber (SR), ethylene propylene diene monomer (EPDM), fluoro rubber (FR), nitrile rubber (NBR), and copolymeric resin (CR).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some scholars have studied the preparation process of flexible composites in recent years. [13][14][15] Hou et al 16 investigated the effect of vulcanization temperature and strain on the mechanical properties of silicone rubber materials. It was found that the tensile strength of silicone rubber cloth increased and then decreased with the increase of vulcanization temperature, which also greatly influenced the compressive mechanical properties.…”
Section: Introductionmentioning
confidence: 99%